Exploring labour-management partnership in NHS Scotland - Zhou, Xiaoguang (2012)
The past few decades have witnessed a change from traditionally adversarial labour-management relations to a new type of partnership arrangement in British industrial relations in some organisations. It is expected that such arrangement may provide an opportunity for Britain unions to return from political and economic exile, and secure mutual gains for the primary parties to the employment relationship.